2016
DOI: 10.2215/cjn.06200615
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Concentration, Acid-Base Status, and Mortality in the Health, Aging, and Body Composition Study

Abstract: Background and objectives Low serum bicarbonate associates with mortality in CKD. This study investigated the associations of bicarbonate and acid-base status with mortality in healthy older individuals.Design, setting, participants, & measurements We analyzed data from the Health, Aging, and Body Composition Study, a prospective study of well functioning black and white adults ages 70-79 years old from 1997. Participants with arterialized venous blood gas measurements (n=2287) were grouped into ,23.0 mEq/L (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 44 publications
5
68
0
2
Order By: Relevance
“…Finally, we did not have a complete description of the acid-base status of the patients (pH, PCO2 and bicarbonate level) and thus we do not know if the patients with higher serum bicarbonate levels were alkalemic. Studies have shown that patients can have alkalemia or acidemia with various serum bicarbonate concentrations [18] and future studies should obtain a complete acid-base profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we did not have a complete description of the acid-base status of the patients (pH, PCO2 and bicarbonate level) and thus we do not know if the patients with higher serum bicarbonate levels were alkalemic. Studies have shown that patients can have alkalemia or acidemia with various serum bicarbonate concentrations [18] and future studies should obtain a complete acid-base profile.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also found that metabolic acidosis results in activation of the renin-angiotensin aldosterone system and vascular endothelial dysfunction [3]. Epidemiologic studies have found that lower serum bicarbonate concentrations are associated with incident and prevalent hypertension [46], insulin resistance [7,8], kidney disease progression [916] and mortality [1418]. Collectively these data suggest that metabolic acidosis may be a risk factor for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also show an important correlation between abnormal acid-base homeostasis and increased mortality [3]. …”
Section: Introductionmentioning
confidence: 99%
“…This study showed a U-shaped association between S-bicarbonate and mortality as well as ICU length of stay. Another recently published study investigated the associations of bicarbonate and acid-base status with mortality in healthy older individuals [3]. This study showed that metabolic alkalosis was associated with higer mortality.…”
Section: Introductionmentioning
confidence: 99%